The Duality of Village Fund Provision: An Analysis of the Balance of Opportunities and Challenges in Community Economic Empowerment (Tului Village Case Study) - Karjo Nalu; Isra Muksin (Yayasan Ilomata, 2026)
The Village Fund Policy is a step taken by the government to accelerate development and improve the quality of life of rural communities, through strengthening the economy and creating sustainable job opportunities. The purpose of this study is to get an overview of the evaluation of opportunities and challenges for economic empowerment policies of the Tului Village community. The method used in this study is qualitative with a case study approach, the research was conducted in Tului Village using observation techniques, in-depth interviews, and documentation in data collection. The results of the study show that in terms of opportunities through basic infrastructure, village funds are used for agricultural roads and business capital. Meanwhile, the challenge is that the management of village funds in Tului Village has not implemented the principles of transparency and accountability.